Actor network in tourism management based on sustainable development (Case study of tourism development in Batu City, Indonesia) - Lestari, Asih Widi; Suwitri, Sri; Larasati, Endang; Warsono, Hardi (Management and Entrepreneurship: Trends of Development, 2020)
Batu City is known as one of the leading tourist cities in Indonesia because of its extraordinary potential of natural beauty. The purpose of this research is to analysize the actor network in tourism management based on sustainable development in Batu City. This study used a descriptive research method with a qualitative approach. As a result it is recommended to strengthen the role Department of Environmental Service in tourism development policies in Batu City. Batu City Government needs to establish a forum for “Community Conscious Environment” as a controlling agent. Batu City Government also needs to expand cooperation with academics, especially in environmental assessment cooperation. JEL Classification : A21, I28